The Influence of Human Resource Management Strategies and Job Satisfaction on the Performance of Mobile Coffee SMEs in Medan - Hengky Kosasih; Elyzabeth Wijaya; Susanto Susanto; Devia Febrina; Eddy Harnjo (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
This study aims to examine the impact of human resource management (HRM) strategies and job satisfaction on the performance of mobile coffee small and medium enterprises (SMEs) in Medan. In this study, HRM is measured based on various factors such as HR planning, training, and the development of skills relevant to the operations of the mobile coffee business. Job satisfaction is evaluated based on aspects of rewards, motivation, and relationships among colleagues within the business. Meanwhile, SME performance is measured by sales levels, customer satisfaction, and operational efficiency. The research method used in this study is a quantitative approach with a survey as the data collection technique. The sample consists of 100 mobile coffee SME owners spread across Medan, and data were collected using a questionnaire specifically designed to measure these variables. The data obtained were then analyzed using multiple linear regression techniques to determine the extent to which HRM and job satisfaction affect business performance. The results show that both HRM strategies and job satisfaction significantly influence the performance of mobile coffee SMEs. Improvements in HRM, such as relevant skills training and high work motivation, were found to enhance business performance. Additionally, high job satisfaction also contributed to performance improvement, with factors such as rewards and supportive relationships among employees playing a significant role. These findings imply that effective HRM and achieving high levels of job satisfaction are crucial in driving the success and progress of mobile coffee SMEs in Medan.